Influence of parental involvement on discipline of secondary school students in Kitui Central Sub- County - Kaluma, Cosmus Mutemi (Strathmore University, 2021)
The performances of schools generally rely on effectiveness of the management of learners’ discipline. The purpose of this study was to assess the effect of parental involvement in managing the discipline of the students. The study specifically sought to determine effect of parental social, economic and cognitive involvement on the learners’ discipline. This study adopted a correlational study design. The target population for the study included all the principals, deputy principals, class teachers and students in the 35 public secondary schools in Kitui Central Sub-county. The study used census to select all the 35 principals and deputy principals in Kitui Central Sub-county to participate in the study. Proportionate and purposive sampling was used to select 149 class teachers and 371 learners in form three and four classes. The study relied on data collected though questionnaire structured to meet the objectives of the study. Responses were tabulated, coded and processed by use of a computer statistical package for social sciences (SPSS) version 2.0 programmes to analyze the data. The findings of the study were there was a significant strong positive correlation between parental social involvement and management of discipline of learners. There was a significant strong positive correlation beween parental economic involvement and students’ discipline in public secondary schools. There was a significant strong positive correlation between parental cognitive involvement and student’s discipline (P<0.05). The study concluded that parental involvement in its different forms influenced discipline of learners significantly. The study recommends that parents should limit use of mobile phones and TV in homes, the parents should enquire about students behavior while in school, the ministry of education should in-service school principals on management of students to reduce indiscipline cases in secondary school, the government should increase the amount of funding to schools to include exercise books and writing materials to students from needy families. This would help the students from poor families to have enough learning material hence reduce temptation to steal from the other students, the national and county levels of government ensure and support the 100% transitioning policy for learners so as to finish secondary education. The government should review the use of all disciplinary methods in public secondary schools and provide policy guidelines on parental involvement in the management of students’ discipline in all learning institutions.
Submitted in partial fulfillment of the requirements for the degree of Master’s in Education Management at Strathmore University
Keywords: Students’ discipline; Parental social involvement; Parental economic involvement; Parental cognitive involvement